2010
DOI: 10.1039/b925351c
|View full text |Cite
|
Sign up to set email alerts
|

Silyloxyazadienes: one intermediate and two competitive pericyclic reactions

Abstract: The two competing mechanisms in the reaction of 3-trialkylsilyloxy-2-aza-1,3 dienes to form beta-lactams through a [2+2] electrocyclic ring closure or tetrahydrooxazinan-4-ones via a [4+2] hetero-Diels-Alder reaction were studied using Density Functional computations. Although the [2+2] and [4+2] mechanisms are typical of dienes, their competition, starting from the same diene intermediate, has not yet been observed and analyzed. This competition is governed by a delicate interplay between temperature and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The zwitterionic intermediates 6 are synthetically analogous to the neutral and isolable 3-trialkylsilyloxy-2-aza-1,3-dienes . On one hand, both of them can undergo conrotatory ring closure to form four-membered β-lactams.…”
Section: Resultsmentioning
confidence: 99%
“…The zwitterionic intermediates 6 are synthetically analogous to the neutral and isolable 3-trialkylsilyloxy-2-aza-1,3-dienes . On one hand, both of them can undergo conrotatory ring closure to form four-membered β-lactams.…”
Section: Resultsmentioning
confidence: 99%
“…However, they are to some extent mechanistically different. The former prefers nucleophilic π 4 contatory ring closure and stepwise nucleophilic [4 + 2] annulations to produce β-sultams and 1,2,4-thiadiazinane 1,1-dioxides, respectively, while the latter favors concerted pericyclic reactions, π 4 contatory ring closure and hetero-Diels–Alder cycloaddition, to give rise to β-lactams and 1,3-oxazin-4-ones, respectively …”
Section: Results and Discussionmentioning
confidence: 99%
“…This competition between a [2+2] electrocyclic (EC) reaction and a [4+2] cycloaddition has been already observed by our group with the same diene scaffold and a carbonyl compound as a dienophile. Theoretical studies by density functional computations [36] showed that the competition between the formation of a perhydrooxazinone (arising from a [4+2] HDA reaction) and/or a β-lactam (arising from a [2+2EC] Staudinger reaction) is governed by a delicate interplay between temperature and the very nature of the substituents of the diene and dienophile. Similar computational studies have also been performed in the present case in which there is competition between piperidin-2-one 3f and the β-lactam 4f formation.…”
Section: Entrymentioning
confidence: 99%